Estimation of antioxidative potential of thyme (Thymus alpestris L.) - Ljubica Vasiljević; Mirjana Beribaka; Jelena Vulinović; Slađana Petronić (Journal of Engineering & Processing Management, 2017)
Family Lamiaceae (labia) includes a large number of cosmopolitan speciesincluding Thymus alpestris (Thyme) characterized by the presence of essential oilsand phenolic compounds. It represents a perennial semi-shrubby plant. Theantioxidant potential of thyme is due to the presence of polyphenolic acids andflavonoids. The topic of this paper is the extraction of thyme (Thymus alpestris)with 40% ethanol and 50% ethanol, using Soxhlet method (circulatoryextraction), after which, the content of phenolics and flavonoids was determinedin order to confirm the antioxidant potential of this plant species. The resultsshow that 40% ethanol extract has the highest content of phenolics andflavonoids and the highest antioxidant potential, resultingly.
Keywords: antioxidative potential; flavonoids; thyme; phenols